PERAN AMERIKA SERIKAT DALAM MEMPERKUAT KEBIJAKAN PERTAHANAN JEPANG 2010 - 2012 - Burhan Utomo, - (2017)
This research explains the role of the United States in strengthening Japan's defense policy 2010-2012. The threats that come from the East Asian world begins with North Korea that deliberately creates weapons that can reach the territory of Japan which became one of the alliances of the United States felt that Japan needs help in its defense system to minimize the threat coming from its neighbor. In addition to the threat coming from North Korea, Japan also has a threat coming from the rapid progress of the Chinese military that made Japan felt threatened by the progress of the Chinese military, so the United States took the initiative to help Japan in strengthening its defense. In terms of the Japanese Military does not mean without the help of the United States who became one of the alliance and also as a Super Power as a peacekeeping police in the world